Evaluation of the migration of chemicals from baby bottles under standardised and duration testing conditions. Issue 5 (3rd May 2016) - Onghena, Matthias; Van Hoeck, Els; Negreira, Noelia; Quirynen, Laurent; Van Loco, Joris; Covaci, Adrian
ABSTRACT: After the prohibition of bisphenol-A-containing polycarbonate baby bottles in the European Union (EU), alternative materials, such as polypropylene, polyethersulphone, Tritan™ copolyester, etc., have appeared on the market. Based on an initial screening and in vitro toxicity assessment, the most toxic migrating compounds were selected to be monitored and quantified using validated GC- and LC-QqQ-MS methods. The effect of several 'real-life-use conditions', such as microwave, sterilisation and dishwasher, on the migration of different contaminants was evaluated by means of duration tests. These results were compared with a reference treatment (filling five times with pre-heated simulant at 40°C) and with the legal EU 'repetitive-use conditions' (three migrations, 2 h at 70°C). Analysis of the third migration step of the EU repetitive-use conditions (which has to comply with the EU legislative migration limits) showed that several non-authorised compounds were observed in some baby bottles exceeding 10 µg kg −1 . However, all authorised compounds were detected well below their respective specific migration limits (SMLs). The reference experiment confirmed the migration of some of the compounds previously detected in the EU repetitive-use experiment, though at lower concentrations. Analysis of extracts from the microwave and dishwasher experiments showed a reduction in the migration during the duration tests. In general, the concentrations found were low and comparable with the reference experiment. Similar observations were made for the two sterilisation types: steam and cooking sterilisation. However, steam sterilisation seems to be more recommended for daily use of baby bottles, since it resulted in a lower release of substances afterwards. Repeated use of baby bottles under 'real-life' conditions showed no increase in the migration of investigated compounds and, after some time, the migration of these compounds even became negligible.